Prevalence and predictors to occurrence of adolescent repeat pregnancy among adolescents attending health facilities in Suna East Sub County-Migori Kenya - Oyugi, Samuel O.; Arudo, John O.; Ambetsa, Millicent A. (International Journal Of Community Medicine And Public Health, 2023)
Background: A repeat pregnancy at adolescence often comes with much stress and complications. It feeds into a cycle of deprivation that compromises the life of the young mother and her child. Majority of girls might be having one child but many more might be pregnant or having more than one child at that age. Method: This was a cross sectional mixed method study with semi-structured questionnaires administered to 381 adolescents. Two FGD and 5 key informant interviews were also conducted. Quantitative data was analysed using t-test for continuous variables and chi-square test for categorical data. Results: The 30.4% of adolescents had repeat pregnancy. Adolescents from Luo ethnic group were 50% less likely to have repeat pregnancy. Those who knew at least one method of family planning were 40% less likely to have repeat pregnancy while those who had more than two sexual partners had higher odds of repeat pregnancy (OR: 2.5; 95% CI: 1.1-5.6; p=0.02). Adolescents who used condoms only sometimes were twice likely to report repeat pregnancy. (OR: 1.7; 95% CI: 1.1-2.7; p=0.01) while those whose mother had a child while under 18 years had 50% chance of having a repeat pregnancy. Conclusions: The study established a prevalence of repeat pregnancy at 30.4%. There was significant association between ethnicity, level of contraceptive knowledge and having multiple sexual partners to repeat pregnancy. Adolescents with inadequate support and those whose mother had pregnancy when below 18 years were also significantly at risk of repeat pregnancy.